Contrôle des défauts d’emboutissage par optimisation des efforts serre-flan - Ayed, Lanouar Ben; Delamézière, Arnaud; Batoz, Jean-Louis; Knopf-Lenoir, Catherine (European Journal of Computational Mechanics, 2008)
That paper deals with the optimization of the blankholder forces in deep drawing, the blankholder is made of several zones. The optimal forces applied on those zones are computed to avoid defects during the process (necking and wrinkling of the blank). A necking criterion has been formulated. The optimization procedure uses a response surface computed by a moving lest square technique. The methodology is applied to a front door panel, benchmark at the Numisheet’99 conference.